D’une rive à l’autre de la Méditerranée : mobilités, recompositions et adaptations des groupes juifs aux XIVe et XVe siècles - Jennifer Vanz (L’Année du Maghreb)
The anti-Jewish massacres that took place in the Iberian Peninsula during the summer of 1391 led many Jews to take the road into exile in North Africa. Although historians have been interested in these forced mobilities and their consequences for the organisation of Jewish communities in the Maghreb since the beginning of the 20th century, recent contributions from historiography on the limits of approaches in terms of “culture”, and on the need to question the historical uses of notions of “community” and “minority”, invite us to examine the issue again. Thus, the hypothesis on which our article is based stems from two considerations. On the one hand, the Jewish groups of the Crown of Aragon and those of the Maghreb belong, despite their regular contacts and minority positions, to two distinct social worlds, that of the Crown of Aragon and that of the Maghreb. On the other hand, the place of supposed minority groups arises from a process of categorisation involving co-construction between various actors. The aim of this article is to understand how exiled Jews from the Iberian Peninsula negotiated their arrival in a new social world, that of the Maghreb, and how these forced mobilities redrew the contours of Jewish groups according to political, economic and social rather than religious issues. Through a comparative analysis of Arabic legal collections and rabbinical responsa, this study focuses on the way in which these mobilities were accompanied by the creation of new categories to designate the different groups. Two ways of signifying otherness appear. On the one hand, the Jews exiled from the Iberian Peninsula and their descendants were distinguished by the wearing of a particular garment, the “round cape”. This was not a constraint imposed on them by the Islamic power on their arrival, and seems rather to have been the result of a desire to display their otherness in relation to their co-religionists from the Maghreb, who, in practice, did not distinguish themselves from Muslims by their costume. The religious dimension is therefore not the fundamental reason for the difference in dress maintained by the exiled Jews and their descendants, who seemed to invert the stigma by wearing a costume whose cost proclaimed, first and foremost, their social and economic status. On the other hand, the sources designate different groups through the use of categories linked to territory. The construction of these categories makes plain the question of the relationship to sultanic power and the negotiation by the exiled Jews of their position in the Maghrebi social world. Because many of them belonged to the intellectual and commercial elite, they had the resources to negotiate their position with the sultans, who granted them tax privileges and distinguished them from their co-religionists. The second part of the article examines how this process of categorisation following the arrival of exiles from the Iberian Peninsula was translated into urban dynamics. Where the responsa offer the image of a growing structuring of the habitat into denominational neighbourhoods, the fatwas testify to the mixed nature of the habitat. The hypothesis envisaged here is that the fact of grouping together in a neighbourhood reflected the minority experience lived by exiled Jews in their original social world, the Crown of Aragon, where, from the end of the 13th century, the development of Jewish neighbourhoods accompanied the institutionalisation and communitarisation of Jews. Thus, while the dispersed (due to mixed housing) and low-key (due to the absence of distinctive garments) presence of autochthonous Jews was the norm and remained a reality into the 15th century, the arrival of the Jews from the Crown of Aragon was accompanied by the development of Jewish neighbourhoods and the strengthening of community structures aimed at unifying the different groups. In turn, the greater visibility of “hooded” Jews in the public space could explain the renewed interest shown by Mālikite jurists in issues relating to non-Muslims. The development of “Jewish neighbourhoods” then appears as a spatial translation of these categorisation processes, which, beyond the religious, testify to the political and economic issues that preside over urban dynamics.